Occurrence and conversion of progestogens and androgens are conserved in land plants - Shiko, Glendis; Paulmann, Max Jonas; Feistel, Felix; Ntefidou, Maria; Hermann-Ene, Vanessa; Vetter, Walter; Kost, Benedikt; Kunert, Grit; Zedler, Julie A.Z.; Reichelt, Michael; Oelmüller, Ralf; Klein, Jan (New Phytologist, 2023)
Progestogens and androgens have been found in many plants, but little is known about their biosynthesis and the evolution of steroidogenesis in these organisms. Here, we show that the occurrence and biosynthesis of progestogens and androgens are conserved across the viridiplantae lineage. An UHPLC-ESI-MS/MS method allowed high-throughput analysis of the occurrence and chemical conversion of progestogens and androgens in 41 species across the green plant lineage. Dehydroepiandrosterone, testosterone, and 5α-dihydrotestosterone are plants' most abundant mammalian-like steroids. Progestogens are converted into 17α-hydroxyprogesterone and 5α-pregnane-3,20-dione. Androgens are converted into testosterone and 5α-dihydrotestosterone. 17,20-Lyases, essential for converting progestogens to androgens, seem to be most effective in monocot species. Our data suggest that the occurrence of progestogens and androgens is highly conserved in plants, and their biosynthesis might favor a route using the Δ4 pathway.
CRIS-Team Scopus Importer:2023-08-18
Keywords: androgens; Arabidopsis thaliana; Chlamydomonas reinhardtii; Hordeum vulgare; Physcomitrium patens; progestogens; Spirodela polyrhiza; steroidogenesis